A Comparison of Moringa Stenopetala and C.Arietinum (Cicer Arietinum L) Absorbance Efficiency As A Natural Coagulant For Domestic Wastewater Treatment - Paramasivam, Revathi; Razali, Nor Faizah (Progress in Engineering Application and Technology, 2022)
Domestic wastewater is produced due to the usage of water for various daily activities and it is hazardous to other water sources that receive it such as rivers as it contains various contamination and heavy metals such as Chromium (VI). In this project, Moringa Stenopetala seeds and Kabuli Chickpea have been chosen as natural coagulants to study their efficiency in treating the domestic wastewater that has been collected from the cafeteria of Universiti Tun Hussein Onn Malaysia and their absorbance in removing Chromium (VI). The characteristics of both materials are determined through FTIR, the adsorption efficiency determined through Langmuir and Freundlich and the effectiveness as natural coagulant determined through Jar Test where the physiochemical properties that studied were turbidity, COD and pH value. The Chromium (VI) removal by both M.Stenopetala and Kabuli Chickpea in different dosages determined where 200 mg/L of M.Stenopetala has the highest percentage removal which was 42.44%. M.Stenopetala is more efficient as natural coagulant than Kabuli Chickpea an optimum dosage of 200 mg/L as it has 63% of turbidity removal, 75% of chemical oxygen demand removal and higher efficiency to neutralise the pH level of wastewater in acidic medium.